Meiotic and mitotic behaviour of B chromosomes of ryegrass - Techio,Vânia Helena (2010)
Mitotic and meiotic analyses using conventional and fluorescent stains were employed in plants (accession ETBAZ 055 - origin: Capão do Leão, Rio Grande do Sul State, Brazil) from the Germplasm Active Bank of Ryegrass (Banco Ativo de Germoplasma de Azevém) of Embrapa, for observing the behaviour of B chromosomes. In several meiotic stages, there were observed up to two B chromosomes, which have presented an unstable behaviour regarding their precocious ascension to metaphase I or delays during anaphase I. At the end of the process, the Bs showed predominantly segregation for the nuclei under formation in order to guarantee their propagation. Concerning the cells that comprise the anther tapetum and the root meristems, the B chromosomes have presented a more stable behaviour.